Climate change exacerbates interspecific interactions in sympatric coastal fishes. (5th October 2012) - Milazzo, Marco; Mirto, Simone; Domenici, Paolo; Gristina, Michele; Genner, Martin
Summary Biological responses to warming are presently based on the assumption that species will remain within their bioclimatic envelope as environmental conditions change. As a result, changes in the relative abundance of several marine species have been documented over the last decades. This suggests that warming may drive novel interspecific interactions to occur (i.e. invasive vs. native species) or may intensify the strength of pre‐existing ones (i.e. warm vs. cold adapted). For mobile species, habitat relocation is a viable solution to track tolerable conditions and reduce competitive costs, resulting in 'winner' species dominating the best quality habitat at the expense of 'loser' species. Here, we focus on the importance of warming in exacerbating interspecific interactions between two sympatric fishes. We assessed the relocation response of the cool‐water fish Coris julis (a potential 'loser' species in warming scenarios) at increasing relative dominance of the warm‐water fish Thalassoma pavo (a 'winner' species). These wrasses are widespread in the Mediterranean nearshore waters. C. julis tolerates cooler waters and is found throughout the basin. T. pavo is common along southern coasts, although the species range is expanding northwards as the Mediterranean warms. We surveyed habitat patterns along a thermo‐latitudinal gradient in the Western Mediterranean Sea and manipulated seawater temperature under two scenarios (present day vs. projected) in outdoor arenas. Our results show that the cool‐water species relocates to a less‐preferred seagrass habitat and undergoes lower behavioural performance in warmer environments, provided the relative dominance of its warm‐water antagonist is high. The results suggest that expected warming will act synergistically with increased relative dominance of a warm‐water species to cause a cool‐water fish to relocate in a less‐preferred habitat within the same thermal environment. Our study highlights the complexity of climate change effects and has broad implications for predictive models of responses to warming. To achieve more accurate predictions, further consideration is needed of the pervasive importance of species interactions. We believe these fundamental issues to be addressed to understand the biotic consequences of climate change.